EFL Teachers’ Technological Pedagogical Content Knowledge (TPACK) Competence in Indonesian Madrasahs: A Post-Pandemic Analysis - M. Arif Rahman Hakim (Muslim Education Review, 2025)
This study explores the Technological Pedagogical Content Knowledge (TPACK) competence of English as a Foreign Language (EFL) teachers in Indonesian madrasa during the post-pandemic era. Using a descriptive qualitative design, data were gathered from ten English teachers across five provinces (Banda Aceh, Bengkulu, Salatiga, Palangkaraya and Kendari) through semi-structured interviews, classroom observations and field notes. Data were analyzed thematically through coding, categorization and interpretation aligned with TPACK dimensions. Findings reveal that teachers at the Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MT) levels generally exhibit limited integration of technology in teaching, while those at Madrasah Aliyah (MA) demonstrate higher TPACK competence. The study underscores the role of institutional support, teacher training and resource availability in shaping teachers’ technological readiness. The results provide valuable insights for policy makers and educators seeking to strengthen TPACK-based instruction in Islamic educational settings.